350 EFFECTS OF EXERCISE TRAINING AFTER ESOPHAGECTOMY ON PHYSICAL FITNESS, QUALITY OF LIFE AND TREATMENT OUTCOMES. (14th September 2020) - Simonsen, C; Thorsen-Streit, S; Sundberg, A; Sigmundsdóttir Djurhuus, S; Ehlers Mortensen, C; Qvortrup, C; Klarlund Pedersen, B; Svendsen, L; de Heer, P; Frank Christensen, J
Abstract:  : Treatment for cancer of the gastro-esophageal junction (GEJ) can result in considerable and persistent decrements of physical fitness and health-related quality of life (HRQoL). Accordingly, a strong rationale exits to design interventions aiming at maintaining physical fitness and HRQoL during treatment. We aimed to investigate feasibility and safety of postoperative exercise training for patients with cancer of GEJ. Methods: This follow-up of the PRESET pilot study (NCT02722785) included 49 patients with stage I-III GEJ cancer. The patients were allocated to postoperative exercise or usual care and followed for 1 year. The exercise group was prescribed 12 weeks of twice a week concurrent aerobic and resistance training. We evaluated the effects of exercise training on cardiorespiratory fitness, muscle strength and HRQoL. To assess safety, we recorded treatment outcomes including adherence to adjuvant chemotherapy, hospitalizations and 1-year overall survival. Results: The exercise group improved muscle strength (+23.0 kg Leg press 1RM [95% CI, 12.4 to 33.5]) and cardiorespiratory fitness (+30.7 watt [95% CI, 16.3 to 45.1]). The exercise group had an improved HRQoL at 1-year follow-up (+14.9 points [95% CI, 4.5 to 25.3]). Exercise was safe with no differences in rate of patients receiving adjuvant therapy 87.5% vs. 84.2% (RR 1.04 [95% CI, 0.74 to 1.44]), rate of hospitalizations 36.8% vs. 26.1% (RR 1.41 [95% CI, 0.57 to 3.49]) or 1-year overall survival 80.0% vs. 79.3% (HR 0.87 [95% CI, 0.25 to 3.07]) for exercise and usual care, respectively. Conclusion: Exercise in the postoperative period is safe and may improve HRQoL and physical fitness in patients with GEJ cancer. No differences in prognostic endpoints were observed.